Gereja dan Pemuridan: Pilar Pendidikan Agama Kristen dan Implikasinya bagi Murid Kristus - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Jurnal Pendidikan Agama Kristen (JUPAK), 2021)
Many churches and Christians are still unfamiliar with the practice of discipleship, and even if they are familiar with the term discipleship, there are still many who are reluctant or less serious in making discipleship the core of church ministry. It is for this purpose that this research was conducted. The method used is a literature study from discipleship and church experts which is analyzed to get the root of the problem and concepts that should be according to the Bible so that applications can be drawn for today, especially for Christian education patterns in church discipleship or churches that make disciples. The result of this research is the discovery of several applications that are very important for the perspective of Christian religious education related to the church and discipleship that must be continuously worked on, namely: First, Discipleship is the responsibility of all Christians. Second, Discipleship of the church has a strong impact on the spiritual growth of believers. Third, sending students to make disciples is an effective pattern of Christian education. Fourth, the importance of having a fellow disciple disciple in the same vision.